ANTIOXIDANT ACTIVITY AND BIOGENIC SYNTHESIS OF SELENIUM NANOPARTICLES USING THE LEAF EXTRACT OF ALOE VERA - Vyas, Jay; Rana, Shafkat (International Journal of Current Pharmaceutical Research, 2017)
Objective: The objective of this present study were to the biogenic synthesis of selenium nanoparticles using Aloe vera extract and check it's antioxidant potential by ABTS, DPPH and FRAP assays. Methods: In this study we investigated the clove of Aloe vera, which is used for the synthesis of selenium nanoparticles were characterized by using UV-Visible (UV-VIS) spectrophotometer, Transmission electron microscopy (TEM), Fourier transform spectroscopy (FTIR) and Energy dispersive X-Ray spectroscopy (EDAX) and ABTS, DPPH and FRAP assays for checked it's antioxidant potential. Results: The present study was carried out to synthesis of Selenium nanoparticles using extract of Aloe vera. UV-Vis Spectra at 350 nm with Aloe vera extract and observed as hollow and spherical particles in size ranging 7-48 nm which is found more stable more than two months. EDAX analysis was carried out to check the presoak of Selenium in nanoparticles. Results of EDAX, confirmed its present. TEM and SEAD represented addition evidence of formation of nanoparticles whereas SEAD indicates the particles were crystalline in nature. FT-IR analysis was carried out to identify the possible bio molecules and Aloe vera extract-metal ions interaction responsible for formation and stabilization of selenium nanoparticles. FRAP, ABTS and DPPH assay results sequester that Selenium nanoparticles prepared using Aloe vera extract possess more activity than extract alone. Conclusion: The bio molecules of Aloe veraextract acted as stabilizing as well as capping agent leading to the formation of Selenium nanoparticles. Selenite has been proven to have antioxidant activity and is being used as chemoprevention agent in cancer diagnosis but same time it is toxic also. Elemental Selenium i.e. Selenium nanoparticles are less toxic form of selenium. Â